Stent Implantation May Fail Sometimes in Coronary Complications: Extension of an Iatrogenic Left Main Coronary Artery Hematoma - Burak Acar; Ahmet Arikan; Zeki Talas; Umut Celikyurt; Muhip Kanko (Journal of Tehran University Heart Center, 2022)
Coronary artery perforations and dissections, associated with cardiac tamponade or acute vessel closure, are life-threatening complications of percutaneous coronary intervention. In some cases, subepicardial hematomas could occur and compress the vessel. A 59-year-old woman was admitted to our hospital with chest pain and was diagnosed with non–ST-elevation myocardial infarction. Coronary angiography showed the total occlusion of the diagonal artery. During the intervention, left main coronary artery dissection and intramural hematoma occurred as coronary complications. The left main coronary artery was stented; however, the extension of the hematoma through the ostium of the left anterior descending artery caused further complications. The patient underwent an urgent coronary artery bypass graft surgery and was discharged on the seventh postoperative day.